Research Into Practice: Gray Partridge (Perdix perdix) Restoration in Southern England - Ewald, Julie A.; Sotherton, N. W.; Aebischer, Nicholas J. (Frontiers in Ecology and Evolution, 2020)
Numbers of the grey partridge Perdix perdix, a once common breeding bird in Britain and a traditional quarry species, have declined by over 90% over the last 50 years, with similar declines elsewhere in Europe. Since the 1970s the Game & Wildlife Conservation Trust (GWCT) has investigated the causes of the decline in Britain and identified three main reasons for it. These are the loss of nesting habitat, loss of brood-rearing habitat and increased predation. A nature reserve mindset was not compatible with the conservation of a once widespread species of farmed land such as the grey partridge so the recovery programme for it had to be implemented by and appropriate for farmers and their advisors. Therefore, solutions needed to be costed, ideally supported by subsidy (agri-environmental schemes), pragmatic and simple. This resulted in a grey partridge management package based on scientifically proven recommendations. The challenge has now become persuading farmers and land managers to adopt the package and reverse the decline of this species. An important factor in achieving adoption is attracting subsidy support for some of the management options and providing demonstration sites where farmers can go to see how appropriate and practical management leads to successful recovery of grey partridge numbers. For example, at a landowner-led demonstration site in West Sussex, southern England, partridges went from near extinction to densities providing enough birds in autumn to reinstate a wild grey partridge shoot. These outcomes are disseminated through the GWCT’s Partridge Count Scheme (PCS) and used to motivate others to undertake partridge management. For many PCS members, the opportunity to shoot wild grey partridges while conserving the species has been a strong incentive to undertake the requisite management. The GWCT recovery programme has international resonance, as it offers an example of species conservation that fits in with the Addis Ababa Principles and Guidelines (CBD 2004). At the same time, we document how management for partridges enhances other measures of farmland biodiversity (arable flora, invertebrates, hares) that are otherwise declining. Obstacles to a more widespread adoption of the package among more UK farmers are discussed.